Supporting Factors for the Success of MSMEs in Banjarmasin City - Febrianur, Febrianur; Monry Fraick Nicky Gillian Ratumbuysang; Sharfina Puteri Amima; Ananda Setiawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The significant increase in the growth of MSMEs in Banjarmasin City has not been fully followed by business success because there are still weaknesses in internal factors such as human resources, as well as pressure from external factors such as market competition. This study aims to analyze the influence of internal and external factors on the success of MSMEs with a quantitative approach using multiple linear regression on 100 respondents selected by simple random sampling, with data obtained through questionnaires, observations, and interviews and tested using SPSS 27. The results of the study showed that internal factors had a positive and significant effect on the success of MSMEs with a t-value of 10.506 and a significance value of <0.001. External factors also have a positive and significant effect on the success of MSMEs with a t-value of 10.070 and a significance value of <0.001. Simultaneously, service quality and service innovation have a significant effect on the sustainability of MSME businesses with a Fcal value of 106.488 and a significance of <0.001b. The results of the determination coefficient show an Adjusted R Square value of 0.681. This research is important as a basis for strengthening entrepreneurial character and formulating policies for fostering MSMEs. However, this study has limitations in the number of samples and limited area coverage, so further research is recommended to expand the sample, region, and add other variables to make the results more comprehensive.